Economic problems of healthcare development under the pressure of external sanctions - O. M. Dzhavadova (Вестник Северо-Кавказского федерального университета)
Introduction. Modern healthcare systems are a key factor in socio-economic development, but they face numerous challenges, especially in the context of sanctions pressure. Indirect factors such as inflation, currency fluctuations and slowdown in economic growth have an additional negative impact, which leads to an increased financial burden on healthcare and patients. There is also an outflow of qualified personnel due to a decrease in the income of health workers. However, sanctions stimulate the development of import substitution, innovation and independent production, which emphasizes the need for a strategic approach to reforming healthcare and adapting to new challenges. Goal. Analysis of economic problems of healthcare development under the pressure of external sanctions. Materials and methods. The study is based on the analysis of practice-oriented data on the development of the healthcare economy in Russia from 2022 to 2024. Results and discussion. A review of key economic indicators of healthcare for the period 2022-2024 was conducted, including the dynamics of public funding, the level of investment in medical technologies, indicators of the availability and quality of medical services. It was found that sanctions restrictions significantly complicated the introduction of innovative technologies in healthcare, which affected the competitiveness of Russian medicine in the international arena. At the same time, promising areas of adaptation were identified: development of import-substituting industries, increasing the share of domestic financing and improving public administration mechanisms in the healthcare sector. Conclusion. In the course of the work, it was specified that sanction restrictions significantly complicated the implementation of innovative technologies in healthcare. At the same time, promising areas of adaptation were identified, namely development of import-substituting industries, increasing the share of domestic financing and improving public administration mechanisms in the healthcare sector. At the same time, strategic development of healthcare in the context of sanction pressure requires a systemic approach aimed at increasing the sustainability of the national medical system.